Artificial Intelligence (AI) in Psychiatry - A Summary (Global Journal of Medical Research, 2022)
This bibliographic review appraises Artificial Intelligence (AI) theory's applications in the field of psychiatry. Globally hundreds of millions of people suffer from mental disorders. Hundreds of thousands of people in the world commit suicide and also die from an illicit drug overdose due to addiction. Diagnosis and therapy of psychiatric disorders are complex, and machine/computer diagnostic tools for physicians are urgently needed to bolster their decisionmaking. This study includes various applications AI/machine learning algorithms in various subspecialties of psychiatry. AI/ML-based psychiatry offers better value over conventional psychiatry in mood disorders, learning disabilities, children and adolescents' mental illnesses, and substance abuse. However, numerous implementation challenges of AI in clinical psychiatric practice remain.